3D printable concrete: Mixture design and test methods. (March 2019) - Rahul, A.V.; Santhanam, Manu; Meena, Hitesh; Ghani, Zimam
Abstract: The current study deals with a yield stress based mixture design approach for 3D printable concretes. The mixtures were evaluated based on buildability, extrudability, robustness and tests for structural build-up. For the print parameters (such as pump type, nozzle size and extrusion velocity) used in the study, it was found that both extrudability and buildability could be achieved only when the material yield stress was within a range of 1.5–2.5 kPa. Below this range, the material lacked enough strength to achieve shape stability, while above this range, the extrudabilty of the material was difficult. The robustness of the mixtures was quantified in terms of a variability factor defined in terms of the variation in yield stress with small changes in the superplasticizer dosage. Inclusion of 10% of silica fume, 0.1% of viscosity modifying agent (VMA) and 0.1–0.3% addition of nanoclay resulted in decreasing the variability factor, hence improving the robustness. The structural changes due to thixotropy and cement hydration increased the yield stress with time. This structural build-up was assessed by measuring the yield stress with increasing rest duration. The mixture with silica fume showed the maximum structural build-up while the mixture with VMA showed the least. Heat curves from semi-adiabatic calorimetry and penetration curves were also used to assess the structural build-up. They showed a similar trend to that of the yield stress vs time plots.